Second Hankel Determinant Bound Application to Certain Family of Bi-Univalent Functions - Mohamed A. Mamon; Borhen Halouani; Ibrahim S. Elshazly; Gangadharan Murugusundaramoorthy; Alaa H. El-Qadeem (Axioms)
A novel family of bi-univalent holomorphic functions is introduced by the use of the Lindelöf principle. The upper bound of the second Hankel determinant, <semantics>H2,2(χ)</semantics>, is evaluated. Furthermore, specific results are obtained as special cases of the main conclusion. These cases coincide with certain recently obtained results and improve or enhance specific ones.